Usability and acceptability of ASSESS MS: a system to support the assessment of motor dysfunction in Multiple Sclerosis using depth-sensing computer vision - Morrison, Cecily; DSouza, Marcus; Huckvale, Kit; Dorn, Jonas; Burggraaff, Jessica; C, Kamm; Steinheimer, Saskia; Kontschieder, Peter; Criminisi, Antonio; Uitdehaag, Bernard; F, Dahlke; Kappos, Ludwig; et al. (2015)
Background: Sensor-based recordings of human movements are becoming increasingly important for the assessment of motor symptoms in neurological disorders beyond rehabilitative purposes. ASSESS MS is a movement recording and analysis system being developed to automate the classification of motor dysfunction in patients with multiple sclerosis using depth-sensing computer vision. It aims to provide a more consistent and finer-grained measurement of motor dysfunction than currently possible. Objectives: To test the usability and acceptability of ASSESS MS with health professionals and patients with multiple sclerosis. Methods: A prospective, mixed-methods study was carried out at three centres. After a one-hour training session, a convenience sample of 12 health professionals (6 neurologists and 6 nurses) used ASSESS MS to capture recordings of standardized movements performed by 51 volunteer patients. Metrics for effectiveness, efficiency and acceptability were defined and used to analyse data captured by ASSESS MS, video-recordings of each examination, feedback questionnaires and follow-up interviews. Results: All health professionals were able to complete recordings using ASSESS MS, achieving high levels of standardisation on three out of four metrics (movement performance, lateral positioning, and clear camera view but not distance positioning). Results were unaffected by patients’ level of physical or cognitive disability. ASSESS MS was perceived as easy to use by both patients and health professionals with high scores on the Likert-scale questions and positive interview commentary. ASSESS MS was highly acceptable to patients on all dimensions considered, including attitudes to future use, interaction (with health professionals) and overall perceptions of ASSESS MS. Health professionals also accepted ASSESS MS, but with greater ambivalence arising from the need to alter patient interaction styles. There was little variation in results across participating centers, and no differences between neurologists and nurses. Conclusions: In typical clinical settings, ASSESS MS is usable and acceptable to both patients and health professionals, generating data of a quality suitable for clinical analysis. An iterative design process appears to have been successful in accounting for factors that permit ASSESS MS to be used by a range of health professionals in new settings with minimal training. The study shows the potential of shifting ubiquitous sensing technologies from research into the clinic through a design approach that gives appropriate attention to the clinic environment.